2002
DOI: 10.1172/jci15518
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that fibroblasts derive from epithelium during tissue fibrosis

Abstract: Interstitial fibroblasts are principal effector cells of organ fibrosis in kidneys, lungs, and liver. While some view fibroblasts in adult tissues as nothing more than primitive mesenchymal cells surviving embryologic development, they differ from mesenchymal cells in their unique expression of fibroblast-specific protein-1 (FSP1). This difference raises questions about their origin. Using bone marrow chimeras and transgenic reporter mice, we show here that interstitial kidney fibroblasts derive from two sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
1,043
3
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,185 publications
(1,091 citation statements)
references
References 62 publications
25
1,043
3
15
Order By: Relevance
“…This process has been particularly studied in renal fibrosis. It has been hypothesized that when basement membrane is injured by matrix metaroproteinase, epithelial cells that detach from their basement membrane may enter into epithelial-mesenchymal transition, express HSP47 and other mesenchymal markers and divide as fibroblasts [33][34][35]. Whether this process takes place in the lung in IPF or in other forms of pulmonary fibrosis is largely unknown, but urgent evaluation in vitro and in vivo would be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This process has been particularly studied in renal fibrosis. It has been hypothesized that when basement membrane is injured by matrix metaroproteinase, epithelial cells that detach from their basement membrane may enter into epithelial-mesenchymal transition, express HSP47 and other mesenchymal markers and divide as fibroblasts [33][34][35]. Whether this process takes place in the lung in IPF or in other forms of pulmonary fibrosis is largely unknown, but urgent evaluation in vitro and in vivo would be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…6 During this process tubule cells loose epithelial features and convert to fibroblast-like cells. 3 This epithelial-mesenchymal transition (EMT) is paralleled for example by the expression of fibroblast-specific protein-1(FSP1), 13 heat shock protein 47 (HSP 47) 10,16,21 and a-smooth muscle actin (SMA). 31 In contrast, mesenchymal-epithelial transition (MET) plays an important role, when stem/progenitor cells are applied to support regeneration in acute or chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that epithelial cells contribute to fibroblast accumulation through an epithelial-mesenchymal transition (EMT) in the kidney, lung, and liver, in addition to the proliferation of resident fibroblasts and bone marrow-derived fibroblasts [6]. Experiments in mice have demonstrated that endothelial cells associated with the microvasculature can also contribute to the formation of mesenchymal cells during the course of fibrosis via a similar process known as endothelial-mesenchymal transition (EndMT) [7].…”
Section: Introductionmentioning
confidence: 99%